CLIMATOLOGICAL WATER BALANCE AND ARIDITY INDEX TO MUNICIPALITIES OF THE MICRO-REGION OF GUARABIRA, PARAÍBA - Silva, P. L. F. da; Nascimento, R. de S. (Revista Brasileira de Engenharia de Biossistemas, 2020)
The climate is a limiting factor for agriculture and knowledge of its variability can contribute to minimize crop failures. Aimed with this work evaluate the climatological water balance and estimate the aridity index of cities in the micro-region of Guarabira, Paraíba, with data series from 2000-2019. The climatological water balance proposed by Thornthwaite & Mather (1945) was applied to 14 cities in the micro region of Guarabira, in the Agreste of Paraíba: Alagoinha, Araçagi, Belém, Caiçara, Cuitegi, Duas Estradas, Guarabira, Lagoa de Dentro, Logradouro, Mulungu, Pilõezinhos, Pirpirituba, Serra da Raiz and Sertãozinho. The available water capacity of 100 mm was adopted to determine water storage in the soil. Soil aridity (aI) and humidity indexes (uI) were calculated through the relationship between precipitation and potential evapotranspiration (P/ETP). The period of greatest precipitation was concentrated in the months of June and July, while the water deficit is pronounced between November and December. It was concluded that 42.85% of the cities had a moderate aridity index and that seven cities had the maximum available water capacity in the soil below 80 mm year-1.